The neuroaesthetics of prose fiction: pitfalls, parameters and prospects - Burke, Michael (Frontiers in Human Neuroscience, 2015)
Neuroaesthetics tends not to do literature. To put it more precisely, neuroaesthetics tends not to do literature very often and when it does, it is inclined not to do it with much conviction, belief and rigour. This is not the case in the very many impressive studies that have been conducted on the neuroaesthetics of sister arts such as painting, music, dance, sculpture and the like. Why is this the case and, of greater importance, how can it best be resolved? In this paper, the pitfalls, parameters and prospects of a neuroaesthetics of prose fiction will be explored. The article itself is part critical review, part methodological proposal and part opinion paper. Its aim is simple: to stimulate, excite and energize thinking in the discipline as to how prose fiction might be fully integrated in the canon of neuroaesthetics.